Legal Protection of Traditional Cultural Expressions “Penginyongan” in Banyumas Regency Based on Law No.28 of 2014 concerning Copyright - Niswah, Eva Mir'atun (International Journal of Social Science and Religion (IJSSR), 2024)
Traditional Cultural Expressions (TCE) in Penginyongan are diverse and unique. The uniqueness of Penginyongan culture has distinguished between the Javanese Palace culture (Keraton) and Ngapak culture. This condition makes cultural expressions more tangible to the community as folk art. The protection of TCE in Article 38 of Law No. 28 of 2014 on Copyright mandates the state to inventory existing TCE. However, only a tiny part of Penginyongan TCE in Banyumas Regency has been recorded, namely cowongan and begalan. This research uses a qualitative approach with normative juridical. Institutionalisation in protecting Intellectual Property Rights in Banyumas Regency can be seen in terms of legal substance, structure, and culture. In terms of legal substance, the protection of TEE is shown by the laws and regulations that protect it, although there is no specific law for the protection of TEE. Regarding legal structure, TCE protection in Banyumas Regency is carried out by Dinporabudpar (Department of Youth, Sport, Culture, and Tourism). Still, it has limitations, including in efforts to register Communal Intellectual Property Rights. In terms of legal culture, the protection of TCE in Banyumas Regency has obstacles related to the existing ‘speech’ culture.